1997
DOI: 10.1212/wnl.48.4.911
|View full text |Cite
|
Sign up to set email alerts
|

The risks and benefits of carotid endarterectomy in patients with near occlusion of the carotid artery

Abstract: Some believe that carotid endarterectomy (CEA) for carotid near occlusion is a necessary emergency procedure while others call it dangerous. We used the North American Symptomatic Carotid Endarterectomy Trial (NASCET) data to perform an observational study to examine the safety and benefit of CEA for carotid near occlusion. We divided the data of 659 patients into stenosis groups: 70 to 79%, 80 to 89%, 90 to 94%, and near occlusion. The 106 carotid-near-occlusion patients were subdivided into those with a stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
154
2
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(162 citation statements)
references
References 0 publications
4
154
2
2
Order By: Relevance
“…This level of difference was chosen because it is outside the range of measurement error 33 and because meaningful increments in stroke risk occur between decile levels 34 .…”
Section: Methodsmentioning
confidence: 99%
“…This level of difference was chosen because it is outside the range of measurement error 33 and because meaningful increments in stroke risk occur between decile levels 34 .…”
Section: Methodsmentioning
confidence: 99%
“…4,6,7 Although hypoperfusion and resultant slow flow from carotid disease likely play a role in a subset of strokes occurring in carotid stenosis, plaque instability causing distal embolus may be a relatively more influential etiologic factor for stroke in carotid disease in general. 8 Although multisequence MR imaging characterization of plaque has allowed the in vivo discrimination of high-risk plaque tissue elements, [9][10][11] its use in clinical practice has been limited, given the time, expense, and challenge of performing multisequence carotid plaque MR imaging by using a dedicated carotid coil. CTA-based measurements of soft and hard (calcified) plaque determined on axial CTA source images have recently been proposed as potential simple alternative markers of vulnerable plaque in high-grade ICA stenosis.…”
mentioning
confidence: 99%
“…A comparison of treatment differences indicated that surgery reduces the risk of stroke at 1 year by approximately one-half ( p < 0.001) in patients with near ICA occlusion. [4] In contrast, a report after reanalysis of the final results of the ECST trial concluded that surgery was of little benefit in symptomatic patients with near total occlusion. This study included 125 patients with near occlusion, of whom 78 were treated surgically and 47 medically.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies are conflicting and provide little benefit in clinical decision making. [4,5] Therefore, the aim of the present study was to prospectively evaluate clinical effects of eversion carotid endarterectomy (ECEA) versus best medical treatment of symptomatic patients with near total ICA occlusion.…”
Section: Introductionmentioning
confidence: 99%